Pengembangan Media Pembelajaran Berbasis Game Pilah Sampah dalam Meningkatkan Rasa Peduli Lingkungan Siswa pada Materi Kenampakan Alam di Kelas IV SD - Wahdini Rohmah Jaelani; Yessi Vichaully; Tin Rustini; Yona Wahyuningsih (Departement of Mathematics Education, 2023)
The purpose of this research is to develop learning media based on waste sorting games. This development research was carried out using the Research & Development development model developed by Sugiyono through ten stages, namely potentials and problems, data collection, product design, design validation, design revision, product trial, product revision, usage trial, product revision, and product resulting from. The target of this research is the fourth grade elementary school students who are studying natural appearance material. The results of this study are that the development of learning media is very interactive and can be used as a supporting medium to increase students' sense of environmental care.